2018
DOI: 10.5935/abc.20180194
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Oxidized Lipoprotein of Low Density in Users of Combined Oral Contraceptives

Abstract: BackgroundThe use of combined oral contraceptive (COC) has been related to changes in glycemic, lipid metabolism, increased oxidative stress, and systemic blood pressure, which could suggest a higher oxidation of low-density lipoprotein cholesterol (LDL-cholesterol) in women on use of COC.ObjectiveTo test the hypothesis that there is a difference in the plasma values of oxidized LDL among women who use and do not use COC, as well as to evaluate the correlation between it and the lipid profile and high-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 33 publications
1
10
3
2
Order By: Relevance
“…Several studies have demonstrated that OC use for healthy women increases oxidative stress [ [18] , [19] , [20] ]; however, mechanisms remain unclear. One possible explanation is that, in contrast to E2, ethinylestradiol (EE) does not protect endothelial cells against oxidative stress and does not increase nitric oxide (NO) production [ 21 ].…”
Section: Commentsmentioning
confidence: 99%
“…Several studies have demonstrated that OC use for healthy women increases oxidative stress [ [18] , [19] , [20] ]; however, mechanisms remain unclear. One possible explanation is that, in contrast to E2, ethinylestradiol (EE) does not protect endothelial cells against oxidative stress and does not increase nitric oxide (NO) production [ 21 ].…”
Section: Commentsmentioning
confidence: 99%
“…This expands lipid development in the liver causing a rise in VLDL-C levels [29]. The positive age-related relationship with VLDL-C proved by delayed utilization of estrogen is supported by the solid positive relationship of term with VLDL-C. VLDL-C levels were higher and increment with age and term of pill use [30].…”
Section: Resultsmentioning
confidence: 99%
“…(15,26,31) In other publications, the correlation of increased CRP in contraceptive users was not considered. (20,33)…”
Section: Changes In Pcrmentioning
confidence: 99%